Delayed Diagnosis: Tuberculous Arthritis of Right Knee Joint in a Patient with Rheumatoid Arthritis - H. Senarathna; K. Deshapriya (Case Reports in Rheumatology)
Background. Though skeletal tuberculosis (TB) accounts about 3% of all TB cases, it occupies 10–35% of extrapulmonary TB cases. Common osteoarticular sites involved include the spine (40%), hip (25%), and knee (8%). Co-occurrence of rheumatoid arthritis (RA) and tuberculous arthritis involving peripheral joint is rarely reported in the literature. Case Presentation. We present a case of 42-year-old Sri Lankan-Sinhalese male with right knee joint pain and swelling for one-year duration. This patient had a history of long-standing RA with interstitial lung disease for which he was on multiple immunosuppressive medications including methotrexate, sulfasalazine, leflunomide, mycophenolate mofetil, and prednisolone. His knee joint aspiration fluid was positive for both acid fast bacilli (AFB) and polymerase chain reaction for TB (TB-PCR). He was started on anti-tuberculous chemotherapy. Conclusion. TB should be considered as an important differential diagnosis for chronic mono-arthritis of knee joint with a high degree of suspicion, particularly where TB is endemic.